Control of 7-phase permanent magnet synchronous motor drive post three failures - Kamel Saleh; Mark Sumner (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The article is introducing a new control technique for the 7-phase permanent magnet synchronous motor (PMSM) drive to enhance its robustness against the failure of phases ‘a’ and ‘c’ in addition to the failure of the encoder occurring simultaneously. The article is firstly developing a new multi-dimension space vector pulse width modulation (SVPWM) technique as a part of the fault-tolerant control technique (FTC) to control the magnitudes and angles of the motor’s current after the failures of phases ‘a’ and ‘c’. Moreover, the paper is developing another FTC to obtain a sensorless operation of the 7-phase motor after the failure in the encoder while the phase ‘a’ and ‘c’ are faulted based on the tracking of the saturation saliency. Simulation results prove that the ripple in the speed post the three failures was maintained to be less than 10 rpm compared to 2 rpm when the 7-phase drive is running without faults. In addition to that, the results demonstrated that the motor responded to instant changes in speeds and loads with a dynamic response very close to that obtained when the 7-phase motor ran under healthy operating conditions.